Language Style in “What A Girl Wants” Movie - Muhammad Iqbal Ramdhani; Shynta Amalia; Yanti Purnama Sari (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2020)
The objective of this study is to analyze the language style using the theory of Martin Joos. This study aims to find out the kinds of language styles used in movie and to identify the dominant language style used by the main characters in the movie. This study used the descriptive method. The data were collected through utterances of major characters in the movie. The results show two main points. The first finding relates to the kind of language styles used in the movie; formal style, casual style, consultative style, and Intimate style. The second finding is the dominant language style; casual style and intimate style. In accordance with the findings, the researchers would like to suggest to further researchers to analyze other elements of language style, such as the functions language style.